1995
DOI: 10.1099/13500872-141-8-1985
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of exogenous ferric iron by a surface-associated ferric reductase of Listeria spp.

Abstract: The reduction of exogenous ferric iron by Listeria monocytogenes, a Grampositive food-borne pathogen, was investigated. Using an assay incorporating the ferrous iron chelator ferrozine, we showed that intact cells of L. monocytogenes, when exposed to ferric iron, were able to rapidly reduce and solubilize the iron to the ferrous form. Reduction occurred only after direct contact between the bacteria and the iron source. A number of different ferric iron chelates, including transferrin and lactoferrin-bound iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 31 publications
2
63
1
Order By: Relevance
“…Secreted Fe 31 reductants have been described for several bacteria (Adams et al, 1990;Homuth et al, 1998) and for yeasts (Dancis et al, 1990;Nyhus et al, 1997). Precedence for membrane-associated Fe 31 reductase activities also exists (Dailey and Lascelles, 1977;Fischer et al, 1990;Deneer et al, 1995;Mazoy and Lemos, 1996). It was postulated in the study of Worst et al (1998) (Fig.…”
Section: H Pylori Feob Mutants Do Not Colonize a Mouse Model Of Infementioning
confidence: 99%
“…Secreted Fe 31 reductants have been described for several bacteria (Adams et al, 1990;Homuth et al, 1998) and for yeasts (Dancis et al, 1990;Nyhus et al, 1997). Precedence for membrane-associated Fe 31 reductase activities also exists (Dailey and Lascelles, 1977;Fischer et al, 1990;Deneer et al, 1995;Mazoy and Lemos, 1996). It was postulated in the study of Worst et al (1998) (Fig.…”
Section: H Pylori Feob Mutants Do Not Colonize a Mouse Model Of Infementioning
confidence: 99%
“…14) It has been shown that some bacteria, like L. monocytogenes which does not produce any siderophore, can use the exogenous siderophores and catechol ligands produced by other bacteria 15) or can express a surface-associated ferric reductase. 16) Another mechanism for the antibacterial activity of lactoferrin, which is independent of its iron saturation, is the direct binding of lactoferrin to the bacteria. With Gram-negative bacteria, lactoferrin induces the rapid release of lipopolysaccharide (LPS), damaging the outer membrane and increasing its permeability.…”
mentioning
confidence: 99%
“…Although Listeria does not produce siderophores, it is able to obtain iron using either exogenous siderophores produced by other micro-organisms or natural catechol compounds widespread in the environment (Jin et al, 2006;Xiao et al, 2011). Physiological data suggest the existence of strong surface-associated ferric reductase activity in L. monocytogenes (Deneer et al, 1995;Cowart, 2002), but no genetic determinant for the enzyme has been identified in its genome. The reduction of iron from ferric to ferrous is critical because ferric iron is insoluble and is not possible to mobilize in its unbound state.…”
Section: Introductionmentioning
confidence: 95%
“…Ferric reductase activity in the tatC and fepB mutants L. monocytogenes has been shown to have a strong surfaceassociated ferric reductase enzyme (Deneer et al, 1995;Cowart, 2002). However, genome searches for homologous sequences encoding ferric reductase enzymes in other Gram-positive bacteria did not show any significant homology.…”
Section: Tat-signal Peptide In Fepbmentioning
confidence: 99%
See 1 more Smart Citation